Syair dalam Pendidikan Islam Madrasah As’ad Jambi Seberang 1944-1970 - Nirwan Il Yasin; Siti Syuhada (Islam Transformatif : Journal of Islamic Studies, 2020)
Researchers and academicians have indeed done a lot of researches in Jambi. The aspects of the life the society of Jambi Seberang in all any studies have been carried out, one of them is historical studies. The research process was also carried out by involving in-depth studies which became a reference to previous studies in this research. The rhyme is one of the Jambi education learning process in the Jambi Seberang area that still needs to be revealed. This awareness also wants to be built in the midst of the many educational patterns that have been adjusted during the times. Rhyme in the 20th century has become a powerful method, in addition to the fact that the people of Jambi have already recognized the repertoire of this rhyme as part of the cultural speech of the people. One of the teachers who uses rhyme in his studies is  teacher Abdul Qodir Ibrahim. This research was using historical methods, namely: Heuristics, criticism, interpretation, and historiography. The disclosure was made so that all forms of educational changes that exist in Jambi society can be appointed as the identity of the Jambi Sebrang society. This disclosure was made in the Jambi Seberang area, which is the first area of Islamic education in Jambi. This investigation tries to explain rhyme in the Islamic education of Jambi community, and the dynamics of its development process. Peneliti dan akademisi memang telah banyak melakukan penelitian di Jambi. Aspek sisi kehidupan masyarakat Jambi seberang dalam kajian apapun telah dilakukan. Salah satunya kajian sejarah. Proses penelitian ini pun dilakukan dengan melibatkan kajian yang mendalam yang menjadi referensi tinjauan terdahulu tentang penelitian ini. Syair dalam proses pembelajaran pendidikan Jambi di wilayah seberang Kota Jambi yang masih perlu untuk diungkap. Kesadaran ini juga ingin dibangun di tengah banyak pola pendidikan yang sudah disesuaikan pada perkembangan zamannya. Syair pada akhir abad 20 menjadi metode yang ampuh, disamping memang secara garis besar masyarakat Jambi telah mengenal khasanah syair ini sabagai bagian dari tutur kebudayaan masyarakatnya. Salah satu Tuan guru yang mengunakan syair dalam pembelajarannya yaitu Tuan guru Abdul Qodir Ibrahim. Dalam penelitian ini menggunakan metode ilmu sejarah yaitu: Heuristik, kritik, intepretasi, dan historiografi. Pengungkapan ini dilakukan agar segala bentuk proses perubahan pendidikan yang ada dalam masyarakat Jambi bisa diangkat sebagai identitas masyarakat Jambi. Pengungkapan ini dilakukan di wilayah Jambi Seberang yang merupakan wilayah pertama pendidikan Islam di Jambi. Dalam penelitian ini mencoba menjelaskan syair dalam pendidikan Islam masyarakat Jambi, dan dinamika proses perkembangannya.